2018
DOI: 10.2147/ijwh.s154212
|View full text |Cite
|
Sign up to set email alerts
|

Self- versus physician-collected samples for the follow-up of human papillomavirus-positive women in sub-Saharan Africa

Abstract: IntroductionHuman papillomavirus (HPV) testing is a suitable tool for primary cervical cancer (CC) screening and follow-up in low-resource settings. Vaginal samples taken by women themselves (Self-HPV) are an interesting alternative to physician-performed sampling (Dr-HPV). Our aim was to assess the performance of Self-HPV and Dr-HPV at 6 and 12 months following a CC screening campaign.MethodsThis study was carried out at the Dschang District Hospital, Cameroon. Women aged 30–49 years were recruited in a CC sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 17 publications
0
30
1
Order By: Relevance
“…In total, 13 of the included studies were cohort studies, and 8 reported cross‐sectional findings in eligible populations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 13 of the included studies were cohort studies, and 8 reported cross‐sectional findings in eligible populations.…”
Section: Resultsmentioning
confidence: 99%
“…The non‐randomized studies recruited populations with different characteristics. For example, Viviano et al., Adamson et al., and Rositch et al . enrolled women with HIV in a cohort study; Toliman et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations